1991
DOI: 10.1128/aem.57.5.1277-1285.1991
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of creosote and pentachlorophenol in contaminated groundwater: chemical and biological assessment

Abstract: Shake flask studies examined the rate and extent of biodegradation of pentachlorophenol (PCP) and 42 components of coal-tar creosote present in contaminated groundwater recovered from the American Creosote Works Superfund site, Pensacola, Fla. The ability of indigenous soil microorganisms to remove these contaminants from aqueous solutions was determined by gas chromatographic analysis of organic extracts of biotreated groundwater. Changes in potential environmental and human health hazards associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(62 citation statements)
references
References 22 publications
(29 reference statements)
6
55
0
1
Order By: Relevance
“…Serial dilutions of creosote and E2 were prepared in dimethyl sulfoxide (DMSO), which was purchased from BDH (Toronto, ON, Canada). [2,4,6, H]17␤-Estradiol ([ 3 H]E2), with a specific activity of 70 Ci/mmol and radiochemical purity Ͼ97%, was purchased from New England Nuclear (Boston, MA, USA). Sesame oil was purchased from Aldon (Avon, NY, USA).…”
Section: Chemicals and Biochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serial dilutions of creosote and E2 were prepared in dimethyl sulfoxide (DMSO), which was purchased from BDH (Toronto, ON, Canada). [2,4,6, H]17␤-Estradiol ([ 3 H]E2), with a specific activity of 70 Ci/mmol and radiochemical purity Ͼ97%, was purchased from New England Nuclear (Boston, MA, USA). Sesame oil was purchased from Aldon (Avon, NY, USA).…”
Section: Chemicals and Biochemicalsmentioning
confidence: 99%
“…Environmental contamination is often associated with surface and groundwater after accidental spillage and improper disposal from creosoting operations, including unprotected drip pads. Creosote-contaminated groundwater has been found to contain high levels of mutagenic, carcinogenic, and teratogenic high molecular weight PAHs [2]. The major source of human exposure to creosote and derived PAHs is through dermal and inhalation routes during occupational use at creosoting operations and production facilities [3].…”
Section: Introductionmentioning
confidence: 99%
“…PAH have been detected in soil, air, water, and sediments [7,9]. PAH are deposited into the aquatic environment through atmospheric deposition, surface runoff, unplanned release of petroleum products, and domestic and industrial sewage effluent [8,[10][11][12][13][14][15]. Some PAH are known to cause acute toxicity in a variety of organisms in combination with solar ultraviolet radiation [16].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of heterocyclic concentrations in sediments may result from losses due to their greater solubility or microbial degradation. Mueller et al [19] demonstrated the rapid biodegradation of nitrogen heterocyclics in creosote-contaminated groundwater. The relative contribution of low molecular weight heterocyclics to the two WSFs differed significantly.…”
Section: Discussionmentioning
confidence: 99%